Legal Protection of Waqf Land Status Against Civil Acts of Individual Nazhir in Lease and Loan Agreements - Nova Monaya; Radif Khotamir Rusli; Ilman Khairi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This article examines the legal protection mechanisms governing the status of waqf land when individual nazhir (trustees) enter into lease (ijarah) and loan-for-use (ariyah) agreements. Although Indonesian Law No. 41 of 2004 on Waqf expressly prohibits the transfer of waqf property rights, the practice of leasing and lending waqf land gives rise to significant legal ambiguities regarding the transfer of management and usufruct rights. This research employs a normative legal methodology using qualitative analysis of statutory regulations, Islamic jurisprudence, and comparative legal frameworks. The findings reveal a complex legal dichotomy: while ownership of waqf land remains perpetual and legally unchanged, the transfer of management and usage rights to lessees and borrowers may constitute a form of rights alienation that potentially conflicts with national regulations concerning waqf protection. Nevertheless, classical Islamic jurisprudence demonstrates greater flexibility by permitting such arrangements, provided that the resulting benefits are directed toward public welfare (maslahah) rather than private interests. This study proposes a comprehensive legal framework that harmonises Indonesian positive law with Islamic legal principles through the establishment of clear standards for nazhir accountability, transparent documentation procedures, and robust oversight mechanisms. By bridging the gap between rigid statutory restrictions and the practical flexibility recognised in Islamic jurisprudence, the proposed framework seeks to ensure that lease and loan agreements function as effective instruments for optimising underutilised waqf assets while fully preserving their perpetual status and original philanthropic purpose.